Uji Aktivitas Antibakteri Fraksi n-Heksan, Kloroform, Etil Asetat Rimpang Bangle (Zingiber casumounar Roxb.) terhadap Staphylococcus aureus - Hamdayani Lance Abidin; Laode Zubaerdhon; Herlina Rante (Fakultas Farmasi Universitas Pancasila, 2022)
The Zingiber casumounar Roxb. It is often used by the public as a traditional medicine for the treatment of rheumatism and throat inflammation. The purpose of this study was to determine the antibacterial activity of the n-hexane fraction, chloroform, and ethyl acetate of the bangle rhizome against Staphylococcus aureus. In this study, antibacterial activity testing of the n-hexane fraction, chloroform, and ethyl acetate of the rhizome of Z. casumounar Roxb was performed. against S. aureus by using the diffusion method. Fractions obtained from the liquid partition results of the ethanol extract 96% of Z. casumounar Roxb. using n-hexane, chloroform, and ethyl acetate. The test results of antibacterial activity of all three fractions indicated the ability to inhibit the growth of S. aureus. Antibacterial activity shows different inhibition zones, namely with an average value in crude extracts of 8.59±0.4 mm, while extracts of n-hexane fractions of 11.67±1.0 mm, chloroform fractions of 11.39±0.6 mm and ethyl acetate fractions of 13.21±0.3 mm. The ethyl acetate fraction had the highest antibacterial activity based on the area of its inhibitory zone.